Metaxenic pollen effect of scab resistant apple cultivars on the fruit of apple - Tóth, M.; Gaál, M.; Bodor, P. (International Journal of Horticultural Science, 2005)
As a part of an apple breeding program, we have examined the pollen effect on the fruit appearance and inner quality of different apple cultivars in the Corvinus University of Budapest Department of Fruit Science. Five apple cultivars (’Golden Reinders’, ’Regal Prince’, ’Rewena’, ’Renora’, ’Idared’) have been crossed by the pollen of some new and some traditional cultivars in our experiment. The measurements were carried out in the analytic and fruit examining laboratory of the Department of Fruit Science. The diameter, height and stem length were measured by digital caliper. We have also examined the squash ratio, soluble solid- and acidic content. Sugar content was calculated by a schedule released by the International Sugar Committee (ISC). From the sugar- and acidic content, we could also count the Pomona-value. We have observed interesting effects according to some attributes in some crossing combinations with the help of statistical analysis. Crossing ’Golden Delicious’ with ’Freedom’, ’Prima’, and ’Baujade’ have resulted in smaller fruit size than other combinations. No significant differences could be observed on `Golden Reinders’ fruits according to metaxenic coloration in the year of the examination. On the other hand the color modifying effect of pollen donating cultivars have manifested on the red fruits of ’Regal Prince’ (Gala Must). `Freedom’ as a pollen donating cultivar has resulted outstanding value in our consistency measurements. Squash ratio was the highest in combinations pollinated by ’Prima’ and `Reglindis’. We have noticed balanced values when measuring inner qualities, only `Reka’ has caused lower acidic content. Significant differences have been found in combinations according to the number of frivolous seeds. No frivolous seeds were found in the combinations ’Golden Reinders’ x ’Freedom’ and ’Idared’ x ’Prima’. Almost two frivolous seeds were found in the fruits of the combination ’Renora’ x ’Sóvári’ in average.